Students Need Analysis in English Learning Materials in Vocational High School - Moh. Fuadul Matin (MEDIASI : Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2023)
Learning English in Vocational High School (SMK) is different from teaching English in Senior High School. In SMK, the orientation is to prepare students to be able to take part in the work field. Consequently, English teachers in vocational school are expected to have the ability to analyze the needs of the students so that they can design an appropriate teaching-learning process. The aim of this study was to identify some factual information about the needs of learning material in vocational students in learning English, especially in the some of language components in English (Vocabulary). The subjects in this study were the vocationalstudents of 2 (two) SMK which organized the TKJ and Hotels Tourism department in Bojonegoro. The results showed that the needs of students towards learning English is to meet the academic professions and the future needs of the students, which involved the skills of the language and some of the language components. Whereas in the case of conformity between the content of the English textbooks and the vocational students’ needs, it was found that the English textbooks was more focused on describing the English language competences generally and not directed to the Department of TKJ and Hotel Tourism itself.